?EFFECT OF AMMONIA AND UREA TREATMENT ON THE IN VIVO DIGESTIBILITY OF MUSTARD SEED HULLS (Biological Sciences - PJSIR, 1994)
Mustard seed hulls (MSH) were treated with 1-5% (w/w) aqueous anunoniaor urea and 20% added water for 45 days at ambient temperature confined system. Under these conditions, the maximum reduction in lignin contents (27.0 and 20.0%) and maximum increase in nitrogen contents (49.2 and 65.0%) was observed when MSH was treated with 5% aq. anunonia and 5% urea respectively. Maximum increase in in vivo digestibility of dry matter, nitrogen crude fibre, minerals and organic matter was observed when MSH were treated with 2% anunonia or 4% urea. The improvement in digestibility indicated that anunonia or urea treated mustrard seed hulls has a great potential as feed ingredient.